CHARACTERIZATION OF THE ORGANIZATIONAL INSTRUMENTS OF THE PINE NUT PRODUCTIVE CHAIN IN RS: A COMPARISON WITH BRAZILIAN CHESTNUTS IN ACRE - Lima Santos, Elke; de Farias, Jorge Antonio; de Campos de Jesus, Luana; Pasa, Débora Luana (Floresta, 2021)
Brazil has a vast diversity of natural resources, which are important in the economic and social context of many families, identified through non-wood forest products (NWFP), among them chestnuts, in the north, and pine nut, in the south of the country. Thus, the objective of the work was to analyze the productive chain of the Brazilian chestnuts in order to establish and identify potentialities existing in its productive chain that can be used to promote the pine nut productive chain in the social, economic and environmental spheres. The study was carried out through the application of an open questionnaire, having as target audience representatives linked to the commercialization and research of both forest products. As a main result, it is evident that the pine nut has an incomplete production chain, presenting itself as a product with secondary representation in the formation of farmers’ income, which contributes to the structure of pine nut commercialization being incipient. In addition, the lack of social organization for extractivism is responsible for the non-consolidation of the chain, coupled with the incipient process of industrialization and processing of the pine nut. which limits the added value of the product. There is a need for greater interest and attention on the part of the government with actions involving entities that can assist in the most different spheres, as well as providing technical assistance, research, and financial support.